Relationship between Organisation Culture and Knowledge Management in SME’s - Cezar-Petre SIMION; Victor RADU (Revista de Management Comparat International)
The article is about the way in which the organisation culture influences the knowledge management in the small and medium-sized enterprises. With the increase of the complexity of the environment in which the SMEs exist, they rely more and more on knowledge as assets and development source. Thus, the organisation culture becomes a mediator between personal knowledge and organisational knowledge, as well as one of the most important factors that condition the knowledge management in SMEs. Among the most important cultural barriers for the knowledge management are: the differences between the declarations and the actions of the managers, the use of the principle ‘knowledge is power’, the apathy in the dissemination of knowledge, the syndrome ‘it has not been invented here’, the language, the mechanistic perception of the organisation, the organisation ‘amnesia’, the over appreciation or under appreciation of the technologies, the attitude ‘knowledge is not an advantage and does not increase for ever’.